A systematic review and meta-analysis of cemented and uncemented bipolar hemiarthroplasty for the treatment of femoral neck fractures in elderly patients over 60 years old - Fu, Mengyu; Shen, Jieliang; Ren, Zhoukui; Lv, Yingwen; Wang, Jiangang; Jiang, Wei (Frontiers in Medicine, 2023)
Background Currently, whether bone cement can be applied in bipolar hemiarthroplasty to treat femoral neck fractures (FNFs) in elderly patients is controversial. The aim of this systematic review and meta-analysis was to compare the effectiveness and safety of cemented bipolar hemiarthroplasty (CBH) versus uncemented bipolar hemiarthroplasty (UCBH) in the treatment of FNFs among elderly patients over 60 years old. Materials and methods The Pubmed, Web of science, Cochrane Library and EMBASE databases were searched comprehensively for relevant articles from their inception to May 2022. Studies about comparing outcomes between CBH and UCBH for FNFs in elderly patients aged more than 60 years were included. Outcomes including operation time, intra-operative blood loss, length of hospital stay, wound infections, residual pain, revisions, re-operations, complications related to prosthesis, general complications, and mortality. The Review Manager 5.3 software provided by the Cochrane Collaboration Network was used to perform the meta-analysis of comparable data. Results A total of 6 randomized controlled trials (RCTs) and 9 observational studies were included in this analysis, with 33,118 patients (33,127 hips). Results of the meta-analysis indicated that the operation time [WMD = 13.01 min, 95% CI (10.79, 15.23)], intra-operative blood loss [WMD = 80.57 ml, 95% CI (61.14, 99.99)], incidence of heterotrophic ossification [OR = 2.07, 95% CI (1,14, 3.78)], were increased in the CBH group but the incidence of intra-operative fractures [OR = 0.24, 95% CI (0.07, 0.86)], periprosthetic fractures [OR = 0.24, 95% CI (0.18, 0.31)], aseptic loosening of prosthesis [OR = 0.20, 95% CI (0.09, 0.44)], wound infections [OR = 0.80, 95% CI (0.68, 0.95)] and re-operation rates [OR = 0.61, 95% CI (0.54, 0.68)] were lower in the CBH group by comparison with the UCHB group. However, there were no significant differences in residual pain, length of hospital stay, prosthetic dislocation, prosthetic subsidence (> 5 mm), acetabulum erosion, revisions, pulmonary infections, pulmonary embolisms, urinary tract infections, deep venous thromboses, decubitus, cardiovascular accidents (arrhythmia/myocardial infarction), and respiratory failure between the two groups. In terms of mortality, perioperative mortality (within 72 h) [OR = 2.39, 95% CI (1.71, 3.32)] and 1-week mortality postoperatively [OR = 1.22, 95% CI (1.05, 1.41)] in CBH group were higher than those in UCBH group, but there were no significant differences in mortality at 1 month, 3 months, 1 year, and 2 years postoperatively between CBH group and UCBH group. Conclusion This meta-analysis found that elderly patients over 60 years old with FNFs who underwent CBH had longer operation time, higher incidence of heterotrophic ossification, intra-operative blood loss, and mortality within 72 h of operation and at 1-week postoperatively, but lower incidence of periprosthetic fractures, aseptic loosening of prosthesis, intra-operative fractures, wound infections and re-operations. Other outcomes were not significantly different between the two groups. Systematic review registration https://www.crd.york.ac.uk/PROSPERO/, identifier CRD42021274253